2011
DOI: 10.1143/jpsj.80.064701
|View full text |Cite
|
Sign up to set email alerts
|

Kondo Effect of a Magnetic Ion Vibrating in a Harmonic Potential

Abstract: To discuss Kondo effects of a magnetic ion vibrating in the sea of conduction electrons, a generalized Anderson model is derived. The model includes a new channel of hybridization associated with phonon emission or absorption. In the simplest case of the localized electron orbital with the s-wave symmetry, hybridization with p-waves becomes possible. An interesting interplay among the conventional s-and p-wave Kondo effects and the Yu-Anderson-type Kondo effect is found, and the ground state phase diagram is d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 45 publications
0
49
0
Order By: Relevance
“…In the same way as the previous studies, 12,13) we consider the situation that the ion vibrates in a one-dimensional potential.…”
Section: Hamiltonian Of the Systemmentioning
confidence: 99%
“…In the same way as the previous studies, 12,13) we consider the situation that the ion vibrates in a one-dimensional potential.…”
Section: Hamiltonian Of the Systemmentioning
confidence: 99%
“…37) Quite recently, the vibration of magnetic ions has been explicitly included in the spinful Yu-Anderson model, and the twochannel Kondo effect has been comprehensively discussed. [38][39][40] not accompanied by any symmetry breaking. 23,24) It has been reported that electric resistivity is in proportion to T 2 for T < T p , while it behaves as / ffiffiffi ffi T p for T > T p .…”
Section: Introductionmentioning
confidence: 97%
“…It also raises the question of weather or not an "electron glass", meaning a coupling between the guest ion dynamics and electronic degrees of freedom, could also be realized in these materials. Indeed, there are some recent theoretical proposals in this direction [9][10][11] . In experiments, there is evidence for an interplay between the rattling motion and quadrupolar fluctuations with the unconventional superconductivity in PrOs 4 Sb 12 12 .…”
Section: Introductionmentioning
confidence: 99%